Resenha: TAVARES, Gonçalo Mendes. Jerusalém. São Paulo: Companhia das Letras, 2006. 228 p. (Revista do Centro de Estudos Portugueses, 2011)
Resenha: TAVARES, Gonçalo Mendes. Jerusalém. São Paulo: Companhia das Letras, 2006. 228 p.